2014
DOI: 10.1589/jpts.26.345
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Working Memory Task and Time on Postural Control of Children with Attention Deficit Hyperactivity Disorder

Abstract: [Purpose] To investigate how balance changes develop across time under different conditions (with or without a memory task) for children with Attention Deficit Hyperactivity Disorder (ADHD). [Subjects and Methods] The participants were 11 children with ADHD and 12 normal children. To determine their static balance ability, a force plate was used to measure the center of the pressure trajectory. [Results] The length of the sway path became slightly greater in both groups when an additional memory task was added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Another finding of this study that showed a significant difference between the experimental and control groups after NPP was the score on executive functions, which significantly increased in the experimental group compared to the control group. The benefits of systematic activities with playful and motor aspects that improve performance in tasks that require inhibitory control and cognitive flexibility in children with ADHD are well documented [48] [49] [50], thus corroborating the results found in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Another finding of this study that showed a significant difference between the experimental and control groups after NPP was the score on executive functions, which significantly increased in the experimental group compared to the control group. The benefits of systematic activities with playful and motor aspects that improve performance in tasks that require inhibitory control and cognitive flexibility in children with ADHD are well documented [48] [49] [50], thus corroborating the results found in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Whether the diagnosis of DCD can be predicted by screening for early fine motor skills, and whether the severity of DCD may be reduced by means of intervention on influencing factors constitute interesting areas to explore 30 ) .In addition, attention-deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder that affects 3–7% of preschool and school-aged children. It has been suggested that the deficits of ADHD children in memory performance, and the inability to allocate sufficient attention to postural control may contribute to the trend of further deteriorating fine motor skills with postural balance 31 , 32 ) . Lee et al 33 ) suggested that complex interactions between multiple risk factors such as physical fitness levels of children are responsible for ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since it is a high impact exercise that requires individuals to jump up and down, it is especially effective at improving balance, coordination, accuracy, explosive muscle strength, and agility. Gappmaier et al 17 ) reported that ball exercises are primarily used in physical therapies for patients with neurological problems, and that they improve the strength of the back muscles 18 ) . The discrepancies in the findings could be due to the differences in exercise type, measuring area, participants, etc.…”
Section: Discussionmentioning
confidence: 99%